Assessment of psycho-educational needs in a clinical sample of children with sickle cell disease. - Peterson CC; Palermo TM; Swift E; Beebe A; Drotar D (Children's Health Care)
Sickle cell disease (SCD) is associated with impaired cognitive and academic functioning, yet prevalence rates of educational needs and accommodations are not known. The Hematology-Oncology Psycho-Educational Needs Assessment was administered to 72 parents of youth, ages 5 to 17, with SCD. Half of the parents identified concerns about their children's learning; however, only 36% had undergone testing for learning problems, and only 26% had individualized education plans. Many parents (33%) reported concerns about attention/memory, and 36% of youth had failed a grade. Of 33 participants referred for neuropsychological evaluation, only 13 completed testing, which revealed below-average IQ and achievement scores. Considerable morbidity was reported; one third of participants missed over 20 school days per year, and 42% reported disease-related difficulties participating in school. Many youth with SCD present cognitive, academic, and functional difficulties, for which universal screening may promote earlier detection and psycho-educational intervention.